Upaya Peningkatan Perekonomian Jemaat BKPN Melalui Hasil Pengolahan Limbah Batang Pisang (Suatu Pelayanan Berbasis Mazmur 104:14) - Alvius Wau; Senida Harefa (Jurnal Teologi Cultivation, 2021)
Abstract So far, banana tree trunk waste is considered as something that is wasted, not to be used as a material with high economic value. Whereas waste banana tree trunks are materials that are easily found amid rural congregations. This study aims to improve the economy of the BKPN congregation through the utilization of banana tree trunk waste. With an understanding of the utilization of banana stem waste as a source of economic income for the congregation, the congregation will have a mindset right about the utilization of banana stem waste and can apply it effectively. The research data were collected using the Observation and techniques Field notation in their search method Participatory Appraisal Research (PAR) because the study involved local rural congregations. The target congregation that will be used as partners in the productive age congregation who has the desire to do business but does not yet have special skills in utilizing banana stem waste. The results of the research on the production process of banana tree trunk waste can reduce wasted waste and can become a new source of income so that it can increase the economic and aesthetic value and function of the waste for the congregation.Keywords: Economy, congregation, waste, banana stemsAbstrakSelama ini, limbah batang pohon pisang dianggap sebagai sesuatu yang terbuang, bukan untuk dimanfaatkan sebagai bahan material yang bernilai ekonomis tinggi. Padahal limbah batang pohon pisang bahan yang mudah ditemui di tengah-tengah jemaat pedesaan. Penelitian ini bertujuan untuk meningkatkan perekonomian jemaat BKPN melalui pemanfaatan limbah batang pohon pisang. Dengan adanya pemahaman tentang pemanfaatan limbah batang pisang sebagai salah satu sumber pendapatan ekonomi jemaat, maka jemaat akan memiliki mindset yang benar tentang pemanfaatan limbah batang pisang dan dapat mengaplikasikannya secara tepat guna. dengan Data penelitian dikumpulkan dengan menggunakan teknik Observasi dan Field not dalam metode peneliti Participatory Appraisal Researc (PAR), karena penelitian melibatkan jemaat pedesaan setempat. Jemaat sebagai target yang akan dijadikan sebagai mitra adalah jemaat usia produktif yang memiliki keinginan untuk melakukan usaha namun belum memiliki keterampilan khusus dalam memanfaatkan limbah batang pisang. Hasil penelitian proses produksi limbah batang pohon pisang ini dapat mengurangi pembuangan yang sia-sia dan dapat menjadi sumber pendapatan terbaru sehingga dapat meningkatkan nilai ekonomi dan estetika serta fungsi dari limbah tersebut bagi jemaat.Kata Kunci: Ekonomi, jemaat, limbah, batang pisang